Recent advances in drug discovery against Mycobacterium tuberculosis: Metal-based complexes - Scarim, Cauê Benito [UNESP]; Lira de Farias, Renan [UNESP]; Vieira de Godoy Netto, Adelino [UNESP]; Chin, Chung Man [UNESP]; Leandro dos Santos, Jean [UNESP]; Pavan, Fernando Rogério [UNESP] (Elsevier, 2021)
Metal-based drugs are privileged motifs that act as primary pharmacophores in bioactive compounds for various diseases, including tuberculosis (TB). This potentially life-threatening and extremely contagious infectious disease is caused by Mycobacterium tuberculosis (Mtb). In 2018, TB infected about 10 million people and caused 1.2 million deaths worldwide. A large number of ligands are promising scaffolds in drug design, including heterocyclic, phosphines, schiff bases, thio and semicarbazones, aliphatic amines, cyclopalladated, cyanometallates and miscellaneous. Moreover, several metal-based complexes have been studied for the treatment of numerous illnesses, including infectious diseases. To contribute to drug design, we identified the metal-based organometallic complexes against Mtb. Thus, in this review article, we analysed the recent contributions of metal-based scaffolds for design of new anti-Mtb drugs in the last decade (2011–2020). Besides, metal-based approaches will be presented in order to find out new antitubercular agents.
Keywords: Drug discovery; Metal-based drugs; Mycobacterium tuberculosis; Tuberculosis